2019
DOI: 10.1103/physrevlett.122.127204
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Observation of the Er- and Fe-Sublattice Magnetization of FerrimagneticEr3Fe5O12

Abstract: X-ray magnetic circular dichroism (XMCD) studies at the Er L 2;3 edges of Er 3 Fe 5 O 12 exhibit a change of the spectral shape as a function of temperature and magnetic field. Using singular value decomposition, this variation is understood as a linear combination of two components. The dominating component is associated with the Er magnetization, while the second contribution is identified as an induced signal from the Fe sites. XMCD at either of the L edges in Er 3 Fe 5 O 12 provides information on the net … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 23 publications
2
21
0
Order By: Relevance
“…Finite intensity of these lines indicate the spin-canting and one can expect the spin-canting in garnets because of the following. The competition between H ext that always tend to align all the moments parallel to it and the AFM super-exchange interaction between the sublattices result a field induced spin-canted phase between R 3+ and resultant Fe 3+ , across T Comp [13,23,24]. This seems to be the case for HoIG sample, wherein a small canting is observed even at 5K.…”
Section: Resultsmentioning
confidence: 91%
“…Finite intensity of these lines indicate the spin-canting and one can expect the spin-canting in garnets because of the following. The competition between H ext that always tend to align all the moments parallel to it and the AFM super-exchange interaction between the sublattices result a field induced spin-canted phase between R 3+ and resultant Fe 3+ , across T Comp [13,23,24]. This seems to be the case for HoIG sample, wherein a small canting is observed even at 5K.…”
Section: Resultsmentioning
confidence: 91%
“…The direct evidence can be seen from the peak shape of the XMCD signal. It does not change with field; only its amplitude gets modified, unlike garnet oxides [41,42], where the L-edge XMCD line shape and the amplitude change with field due to contributions of comparable strength from both 4 f and 3d ions. In the case of intermetallic compounds composed of a 4 f rare earth and a 3d transition metal, an earlier study reported a sizable transition-metal contribution as well to the rare-earth L 2 edge [43].…”
Section: B High-field X-ray Magnetic Circular Dichroismmentioning
confidence: 93%
“…Lock-in frequency was 13 Hz, and the time constant in the lock-in amplifier 100 ms. Bottom: XMCD amplitude as a function of magnetic field for GdCo 2 , with fixed energy at the XMCD peak of the Gd L 3 -edge. combined with this instrumentation will allow XMCD experiments to be performed at very extreme conditions of applied pressure (Mathon et al, 2004;Haskel et al, 2008;Souza-Neto et al, 2009;Baudelet et al, 2009Baudelet et al, , 2010Ishimatsu et al, 2003Ishimatsu et al, , 2011Ishimatsu et al, 2016) as well as low temperatures (<1 K) and high magnetic fields (> 10 T) (Uemoto et al, 2001;Strohm et al, 2019). This will allow a plethora of opportunities to study magnetic materials based not only on rare-earth and 3d transition metals but also on 4f metals (Souza-Neto et al, 2009), 5d metals Veiga et al, 2015), as well as on actinide-based materials (Okane et al, 2008;dos Reis et al, 2017).…”
Section: Figurementioning
confidence: 99%